Feasibility Study of Sago (metroxylon) business : Case study of Sagu Entrepreneurs in Aketobololo Village, Obah District, Central Tidore City, Islands - Muhlis, Asrul; Azizah HS, Nur; Ramli, Abdul Aziz (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This study aims to determine the feasibility of the sago plantation business in Aketobololo Village, Oba Tengah District, Tidore Islands City. Sago sampling was taken using the saturated sample method, namely determining the sample by taking the entire population of sago entrepreneurs in Aketobololo Village, totaling 10 (ten) respondents. The data analysis used is qualitative and quantitative data with the data sources used are primary and secondary data. The analytical tools used are income analysis and business feasibility analysis. The results showed that in Aketobololo Village, Oba Tengah District, Tidore Islands City, the total production obtained by sago entrepreneurs in one year 2022 was 6,240 tumang with a selling price of IDR 120,000-130,000/tumang. So the total amount of income earned by sago entrepreneurs is IDR 724,636,548 in one year of tumang sago production. With an average total income earned by sago entrepreneurs of IDR 72,463,655. The feasibility of the sago tumang entrepreneur is 122, so the sagau business run by the sago entrepreneur is worth farming because the R/C value is more than one.